Pengaruh Struktur Modal Dan Profitabilitas Terhadap Nilai Perusahaan Perbankan Syariah Di Indonesia - Wahab, Abdul; Alwan, Didik (Journal of Sharia Economy and Islamic Tourism, 2021)
Abstract: Every company has the same goal both short and long term that is to maximize and increase the prosperity of the shareholders. To achieve this, then the path that can be taken by the management company is to increase the profits obtained and maximize the value of the company. The purpose of this research is to know the influence of capital structure (DAR, DER) and profitability (ROA, ROE) to company value (EPS) in syariah banking at Indonesia Stock Exchange period 2012-2016. The population of this study is the Sharia (BUS) Commercial Bank listed on the Indonesia Stock Exchange 2012-2016. Method of determining the sample by purposive sampling method, with some criteria that have been determined then the number of samples is as much as 6 Sharia Commercial Banks. The research data is secondary data obtained from Annual Report (AR) year 2012-2016. Data analysis technique used in this research is panel data regression analysis. The results obtained in this study indicate that: 1) DAR has no significant and significant effect on firm value, 2) DER has a significant positive effect on firm value, 3) ROA has no effect on firm value, 4) ROE has no effect on firm value